2009
DOI: 10.4314/njnpm.v12i1.45664
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment Of Total Phenolic Content In Selected Medicinal Plants

Abstract: This study was to compare the total phenolic (TP) content in extracts from eleven plant materials collected at different geographical locations in Kenya, Nigeria, and USA. These plants have been selected because the majority of them are highly pigmented, from yellow to purple, and would therefore have economic value in industries for producing antioxidants and surfactants. Two of them were collected from the industrial and domestic waste outlets. Each analysis was achieved using the Folin-Ciocalteau technique.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
6
1
1
Order By: Relevance
“…TPCs of the selected plant parts of ethanolic extracts were observed in the order: TB leaf>PA leaf> PA stem>TB stem>AP leaf>EP leaf>AP stem>CL leaf>BD leaf>TB bark> MP leaf>CL ripe rhizome> CL unripe rhizome. In a similar study, the total phenolic content of C. longa and E. prostrata were reported as 15.33 mg of GAE/g [24][25][26] which had lower values compared to our results. But in another study the total phenolics in C. longa was reported as 67.9 mg of GAE/100g [27] and 1.22 mg of GAE/100g [28], much lower than our values.…”
Section: Total Phenolic Contentcontrasting
confidence: 55%
“…TPCs of the selected plant parts of ethanolic extracts were observed in the order: TB leaf>PA leaf> PA stem>TB stem>AP leaf>EP leaf>AP stem>CL leaf>BD leaf>TB bark> MP leaf>CL ripe rhizome> CL unripe rhizome. In a similar study, the total phenolic content of C. longa and E. prostrata were reported as 15.33 mg of GAE/g [24][25][26] which had lower values compared to our results. But in another study the total phenolics in C. longa was reported as 67.9 mg of GAE/100g [27] and 1.22 mg of GAE/100g [28], much lower than our values.…”
Section: Total Phenolic Contentcontrasting
confidence: 55%
“…These previous findings corroborate the present results, in which HECLex presented low antioxidant capacity. Similar results were reported previously (Johnson et al, 2008) in which phenolic components of different plants and a crude extract of C. longa were evaluated, with values that were similar to the present study.…”
Section: Boletín Latinoamericano Y Del Caribe De Plantas Medicinales Y Aromáticas/ 62supporting
confidence: 92%
“…Awoyinka et al (2007) mention that C. aconitifolius dried leaves were ground in a mortar and that the extraction was carried out with 96% ethanol for 3 h. The resulting solution was placed in a rotoevaporator at 30°C for 25 min, then placed in a drying oven at 45°C until a constant weight was reached. Johnson et al (2008) reported placing a mixture of 5 g of C. aconitifolius dried leaf in 40 ml of an ethanol/acetone/water/acetic acid solution (40:40:20:0.1 v/v), in a water bath at 60°C for 1 h. Mordi and Akanji (2012) mention that the air-dried powder from C. aconitifolius leaves (1 kg) of fresh matured C. aconitifolius were extracted by percolation at room temperature with 70% ethanol (EtOH). A leaf extract from C. aconitifolius was concentrated under reduced pressure (bath temperature 50°C) and finally defatted with nhexane.…”
Section: Aconitifoliusmentioning
confidence: 99%